THE IMPACT OF THE EUROPEAN COURT OF HUMAN RIGHTS IN DEALING WITH COMMUNIST PAST IN EUROPE - Krtolica, Marko (Ss. Cyril and Methodius University in Skopje - Iustinianus Primus Faculty of Law in Skopje, 2020)
From the ashes of the Second World War, the concept of transitional justice was born. Without any doubt, the development of the concept of transitional justice represents one of the most dramatic events in legal and political science theory. Defined as a determination to face problematic (repressive or conflict) past filled with serious and systematic violations of human rights, the concept of transitional justice among the majority of scholars represents a key step in establishing democracy and rule of law in post-conflict and post-repressive societies. However, among transitional justice scholars we can also find arguments that the concept of transitional justice in its essence is retroactive justice and a tool that may be misused for political party purposes and further violations of human rights. Under the button of this theoretical debates about the effects of transitional justice, very often transitional societies are faced with one essential question – what to do with the problematic past: to forgive or to punish. Such question inevitably was raised in post-communist countries in Europe after the fall of communism. In order to help and give direction to this sensitive topic, the Council of Europe adopted a Resolution dedicated on Measures to dismantle the heritage of former communist totalitarian systems. Exactly, in this Resolution, the Council of Europe gave clear recommendations that member states have to confront their totalitarian communist past. Beside recommendations, the Council of Europe also gave clear guidelines on how to implement the process of confronting communist past. Such guidelines have had the aim to secure a framework for confronting communist past in order to promote democracy and not revenge. However, despite such clear guidelines the post-communist countries in Europe very often misused the process of confronting communist past for political-party goals. In that direction, the European Court of Human Rights had a pivotal role in protection of human rights during the processes of confronting communist past in Europe. The European Court of Human Rights was very active as a result of the processes for confronting communist past in post-communist countries in Europe. Most frequently, the cases before the European Court of Human Rights were connected to violation of human rights due to criminal trials, lustration processes and property restitution. With its decisions, the European Court of Human Rights has protected human rights, reduced the space for misuse of the process of confronting communist past in Europe, but also gave clear directions on how these processes should be conducted. That is the main reason why during the analyzes of the processes of confronting communist past in Europe it is impossible not to analyze the role and impact of the European Court of Human Rights on these delicate processes.
Keywords: Democracy, Human Rights, Transitional Justice, Council of Europe, ECHR, Criminal Trials, Lustration, Restitution.